A Bahia como campo - Guimarães, Antonio Sérgio Alfredo (Afro-Ásia, 2023)
Resenha de: SANSONE, Livio. Estação etnográfica Bahia: a construção transnacional dos Estudos Afro-brasileiros (1935-1967). Campinas: Editora da Unicamp, 2022. 317 p.